2014
DOI: 10.1007/s13312-014-0466-0
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of mortality in neonates with meconium aspiration syndrome

Abstract: Meconium aspiration syndrome is associated with significant mortality. Myocardial dysfunction, birth weight, and initial oxygen requirement are independent predictors of mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
44
3
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(57 citation statements)
references
References 13 publications
6
44
3
4
Order By: Relevance
“…80 In a recent trial from India, mortality rate was found to be as high as 26%, with lower birth weight, the presence of myocardial dysfunction, and higher initial oxygen requirement being independent predictors of mortality. 81 Approximately, one third of these deaths in MAS are directly attributable to pulmonary cause, with the remainder being ascribed to accompanying hypoxic ischemic encephalopathy.…”
Section: Future Therapymentioning
confidence: 99%
“…80 In a recent trial from India, mortality rate was found to be as high as 26%, with lower birth weight, the presence of myocardial dysfunction, and higher initial oxygen requirement being independent predictors of mortality. 81 Approximately, one third of these deaths in MAS are directly attributable to pulmonary cause, with the remainder being ascribed to accompanying hypoxic ischemic encephalopathy.…”
Section: Future Therapymentioning
confidence: 99%
“…The mortality rate in newborn infants has been reported between 10 and 40% (4,5). In our study, 14.3% of newborn infants, diagnosed with meconium aspiration syndrome, died.…”
Section: Discussionmentioning
confidence: 45%
“…Meconium aspiration syndrome (MAS) occurs in 1.3% of live births and symptoms range from mild respiratory distress syndrome with auto recovery to progressive respiratory failure, complications and death, and in the most severe cases, respiratory distress, hypoxia, hypercapnia and respiratory acidosis increase, requiring intensive care and mechanical ventilation (1)(2)(3), and 10 to 40% of cases result in infant's death (4,5).…”
Section: Introductionmentioning
confidence: 99%
“…Aspiration of meconium interferes with normal respiratory physiology by causing airway obstruction, chemical irritation, inflammation, surfactant inactivation, meconium induced apoptosis and there is increased risk to develop air leaks, Persistent Pulmonary Hypertension of newborn (PPHN) and sepsis. 8,9 Respiratory distress with marked tachypnea, retractions, grunting, nasal flaring, and cyanosis ensues soon after birth. Affected infants typically have a barrel-shaped chest with an increased anterior-posterior diameter caused by overinflation.…”
Section: Discussionmentioning
confidence: 99%